Impact of cardiac rehabilitation and treatment compliance after ST-segment elevation myocardial infarction (STEMI) in France, the STOP SCA+ study - Laurent, Emeline; Godillon, Lucile; Tassi, Marc-Florent; Marcollet, Pierre; Chassaing, Stéphan; Decomis, Marie; Bezin, Julien; Laure, Christophe; Angoulvant, Denis; Range, Grégoire; Grammatico-Guillon, Leslie (Frontiers in Cardiovascular Medicine, 2025)
IntroductionAcute ST-elevation myocardial infarction (STEMI) is a frequent and serious presentation of acute coronary syndrome. The STOP-SCA+ study aimed to (i) describe 1-year compliance to secondary prevention cardiac tri-therapy and (ii) identify factors associated with negative outcomes 1 year after STEMI, particularly the impact of compliance and rehabilitation care.MethodsPatients who were >18 years old and hospitalized for STEMI in five interventional cardiac centers with the same cardiac registry in one French region (2.5 million inhabitants), between 2014 and 2018, were included. After a probabilistic matching with the National Health Insurance database [Système National des Données de Santé (SNDS), 96% matching], compliance for cardiac tri-therapy was studied: aspirin, P2Y12 inhibitor, and statin. Factors associated with poor outcomes (ischemic complications, death) were analyzed using Cox modeling and those for compliance by logistic regression.ResultsA total of 3,768 patients were included, of whom 84% underwent primary percutaneous coronary intervention. At 1 year, 3,362 had at least one tri-therapy delivery (89.2%), of whom 53% were compliant, and 2,478 patients went to cardiac rehabilitation (65.8%). Death occurred in 130 patients and/or ischemic complications in 194 (total of poor outcomes 8.0%). Compliance was not associated with complications over the year [HR 1.16 (0.86–1.57)], while the absence of cardiac rehabilitation [2.31 (1.73–3.08)] was associated, as well as female sex 1.54 (1.08–2.19), renal impairment [2.87 (1.49–5.53)], initial STEMI clinical presentation [pejorative Killip 2.04 (1.19–3.50)], and LVEF <40% at discharge [2.22 (1.65–2.99)]. Additionally, cardiac rehabilitation was associated with compliance [OR 1.55 (1.34–1.79)].DiscussionPejorative outcomes 1 year after a STEMI represented 8% of cases, mainly related to patient features, the initial clinical presentation, and the absence of access to rehabilitation. Compliance part in patient health outcomes will need further modeling to accurately study its impact. Matching clinical and medico-administrative databases proved to be relevant for assessing outcomes at a large scale.